Blood acidity and metabolic acidosis in hyperglycemia crisis after Rehydration Therapy - Erik Irham Lutfi; Susmiati Susmiati; Eva Dwi Ramayanti (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research is a comparative analytic study. Based on analysis using paired T test p value = 0,000 so that it can be concluded that there is a change in arterial pH before and after administration of rehydration therapy as much as 3000 ml. The mean changes in arterial pH in this study approached normal values ​​(Normal Arterial pH = 7.35 -7.45). Changes in arterial pH close to normal can be interpreted as much as 3000 ml rehydration therapy improve blood perfusion to the kidneys so that it improves kidney function in reducing ketone acid, decreasing ketone acid will reduce the occurrence of acidosis. After administration of rehydration therapy, it is expected that acids and ketones can be excreted, therefore, fluid has an important role in the management of patients with diabetic ketoacidosis (KAD)